THE RELATIONSHIP BETWEEN EMPLOYEE COMPETENCE AND THE SUCCESSFUL IMPLEMENTATION OF A HOSPITAL MANAGEMENT INFORMATION SYSTEM AT ADINDA MEDICAL CENTRE HOSPITAL SIDENRENG RAPPANG REGENCY - Hardiyanti; Sunandar Said; Zulkarnain Sulaiman; Khaeriyah Adri (CV. Fahr Publishing, 2026)
Successful implementation of a Hospital Management Information System (HMIS) depends not only on technological infrastructure but also on the competence of employees who use the system. This study examined the associations between employee motivation, knowledge, and skills and the success of HMIS implementation at Adinda Medical Centre Hospital, Sidenreng Rappang Regency. An analytical cross-sectional study was conducted from February to March 2026 among 103 employees selected by simple random sampling from 138 HMIS users. Data were collected using a structured questionnaire and analyzed using the Chi-square test at a significance level of 0.05. Motivation was significantly associated with successful HMIS implementation (p = 0.042), as were technical skills (p = 0.044). Knowledge was not significantly associated with implementation success (p = 0.845). These findings indicate that willingness to engage with the system and practical operating ability may be more closely related to successful HMIS use than theoretical knowledge alone. Hospital management should strengthen hands-on training, user mentoring, supervision, and motivational support while continuing to improve system reliability and organizational support.